OVARIAN CANCER: MODERN CLINICAL AND DIAGNOSTIC CONCEPT - Arman Khozhayev; Aruzhan Nuraly; Aruzhan Baishegasheva; Zhanerke Yerkhasym; Akmaral Sagiyeva; Madina Imankhoja; Madina Saparkhanova; Moldir Omirbay; Dana Sailaubai; Assemay Kurbanbay; Yekaterina Zayedova (Theoretical Hypotheses and Empirical Results, 2025)
This scientific and analytical work presents modern world and local-regional data on incidence, mortality, lethality and five-year survival rate of such a common oncological pathology as ovarian cancer. The issues of etiology and pathogenesis, modern approaches and principles of complex diagnostics, prospects for improving treatment results, as well as the prognosis are covered in detail. The epidemiological characteristics of this pathology in our republic are given in the context of the regions of the country